2019
DOI: 10.3389/fimmu.2019.02621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Dynamic Behavior of Neutrophils Following Influenza Vaccination

Abstract: Neutrophils are amongst the first cells to respond to inflammation and infection. Although they play a key role in limiting the dissemination of pathogens, the study of their dynamic behavior in immune organs remains elusive. In this work, we characterized in vivo the dynamic behavior of neutrophils in the mouse popliteal lymph node (PLN) after influenza vaccination with UV-inactivated virus. To achieve this, we used an image-based systems biology approach to detect the motility patterns of neutrophils and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 100 publications
0
36
0
Order By: Relevance
“…Intravital microscopy showed the entry of neutrophils into the popliteal lymph node (PLN) via multiple hotspots on HEV following influenza vaccination (Pizzagalli et al, 2019). Moreover, neutrophil positive for influenza virus were tracked entering into the PLN after vaccination and showed over a time of 2 h changes in their dynamic motility with a decrease in instantaneous and mean speed, directionality, displacement, and an increase in the arrest coefficient suggesting an increase in cell-to-cell interactions (Pizzagalli et al, 2019). Five distinct neutrophil migratory behaviors have been observed: flowing, arrested, patrolling, directed migration, and swarming (Pizzagalli et al, 2019).…”
Section: Neutrophil Margination Within the Parenchyma Of The Spleen Amentioning
confidence: 99%
See 2 more Smart Citations
“…Intravital microscopy showed the entry of neutrophils into the popliteal lymph node (PLN) via multiple hotspots on HEV following influenza vaccination (Pizzagalli et al, 2019). Moreover, neutrophil positive for influenza virus were tracked entering into the PLN after vaccination and showed over a time of 2 h changes in their dynamic motility with a decrease in instantaneous and mean speed, directionality, displacement, and an increase in the arrest coefficient suggesting an increase in cell-to-cell interactions (Pizzagalli et al, 2019). Five distinct neutrophil migratory behaviors have been observed: flowing, arrested, patrolling, directed migration, and swarming (Pizzagalli et al, 2019).…”
Section: Neutrophil Margination Within the Parenchyma Of The Spleen Amentioning
confidence: 99%
“…Moreover, neutrophil positive for influenza virus were tracked entering into the PLN after vaccination and showed over a time of 2 h changes in their dynamic motility with a decrease in instantaneous and mean speed, directionality, displacement, and an increase in the arrest coefficient suggesting an increase in cell-to-cell interactions (Pizzagalli et al, 2019). Five distinct neutrophil migratory behaviors have been observed: flowing, arrested, patrolling, directed migration, and swarming (Pizzagalli et al, 2019). During swarming, neutrophils were observed forming clusters that enlarged over time in areas rich in tissue resident macrophages (Pizzagalli et al, 2019).…”
Section: Neutrophil Margination Within the Parenchyma Of The Spleen Amentioning
confidence: 99%
See 1 more Smart Citation
“…3d, e ). To understand if these different neutrophil subsets have distinct biological functions, we analyzed their migratory patterns based on their directionality and arrest coefficient 25 . Indeed, we found that Nβ neutrophils had distinct migratory pattern compared to Nα subset between 4 and 5 h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…To understand better the different dynamics of recruitment of both neutrophil subsets from the primary site of infection to secondary lymphoid organs, we analyzed the expression of the surface markers involved in neutrophil migration and adhesion, such as IL-1 receptor (IL-1R), CXCR2, and very-late-antigen (VLA-4) α4β1. IL-1R has a clear role in neutrophil recruitment to the peritoneal cavity 26 and migration to secondary lymphoid organs 25 . CXCR2 regulates neutrophil release from bone marrow 27 and neutrophil migration in tumor microenvironment and during severe sepsis 28 , 29 ; it has been shown that failure of CXCR2 downregulation controls neutrophil mobilization during inflammation in the peritoneum 30 .…”
Section: Resultsmentioning
confidence: 99%